Functional Polycentrism in Portugal: an evaluation - Goretti Nunes; Isabel Mota; Pedro Campos (European Regional Science Association (ERSA), 2011)
This paper aims at develop an evaluation of the functional polycentrism of Portuguese municipalities. For that purpose, we develop a critical assessment of the concept of polycentrism and functional polycentrism whose assumptions guide most of the policies of regional planning, and present the main methodologies for its evaluation. We then proceed with the evaluation of polycentricism in Portugal, by using the Social Network Analysis and the Cluster Analysis. The study considers the variable `commuting flows home-to-work' and the results suggest that, from 1991 to 2001, the Portuguese urban system presents a network of commuting denser, less centralized, more dispersed and more clustered.
Keywords: 330